Ressocialização e saúde mental de egressas do sistema prisional do Tocantins - Góis, Yanna Biatriz de Oliveira (Universidade Federal do Tocantins, 2022)
This is a conclusion work of the Psychology course at the Federal University of Tocantins at the University Campus of Miracema. The research aimed to investigate the processes of resocialization and its impact on the mental health of graduates of the Prison System of the State of Tocantins, to understand the phenomenon of prejudice and discrimination in the conditions of reintegration in the labor market and to know the risk and health protection factors mental health of women discharged from the prison system in the context of their family and community relationships. In view of the scarce academic production, this work is justified in view of the need to build knowledge about the re-socialization process and its impact on mental health, from a gender, feminist and intersectional perspective. It is a qualitative research, the method used was the case study. The convenience sample included three reports with public interviews of cisgender women from the female prison system in the state of Tocantins and other locations in the country. The interviews were selected from two sources, the first was an online newspaper from the state of Tocantins and the second source was a platform hosted on the website Uol Notícias, published in the years 2019 to 2021. In both sources, women who have graduated reported the impact of post-prison life on mental health. Of the twelve participants, four are from the State of Tocantins. The descriptive analysis of the interviews showed flaws in the re-socialization process, such as lack of structure and adequate physical space already regulated for incarcerated women, impact of isolation on mental health, abandonment of family members, incentive to work in the private sphere without providing autonomy in post-prison, prejudice and discrimination in the reintegration into the labor market, contributing to the life and mental health of the graduates as risk factors. Studying and working in prison, family support inside and outside the prison, and working outside the prison all contribute to protecting the mental health of these women. It is noteworthy that this work intends to contribute to the field of Psychology, in the struggle to guarantee the rights of this population, taking into account the gender and intersectional perspective.